Genotypic‐specific heat shock response of vector susceptibility to Schistosoma mansoni. Issue 8 (18th August 2022) - Spaan, Johannie M.; Leavitt, Nathaniel; Shen, Jessica; Bundy, Taylor; Burrows, Lillian; Ingram, Christopher; Maehara, Thomas R.; Ndungu, Ibrahim; Mutuku, Martin; Owino, George; Odiere, Maurice; Steinauer, Michelle L.
Abstract: Living organisms are vulnerable to thermal stress, which causes a diversity of physiological outcomes. Previous work has shown that the snail vectors ( Biomphalaria glabrata ) of an important human pathogen, Schistosoma mansoni, revert from resistant to susceptible after short exposure to a heat stress as low as 31°C; however, due to lack of replicability among labs and genetic lines of snails, it has been hypothesized that this effect is genotype dependent. We examined the effects of heat shock on the resistance of two species of snail vectors including B. glabrata and Biomphalaria sudanica . We used three different inbred laboratory snail lines in addition to the F1 generation of field‐collected snails from Lake Victoria, Kenya, an area with high levels of schistosomiasis transmission. Our results showed marginal effects of heat shock on prevalence of infection in B. glabrata, and that this response was genotype specific. We found no evidence of a heat shock effect on prevalence of infection in B. sudanica or on intensity of infection (number of infectious stages shed) in either snail species. Such environmentally influenced defense responses stress the importance of considering this unique interaction between snail and parasite genotypes in determining infection dynamics under climate changes.